Copper antimony sulfide thin films by spray pyrolysis for photovoltaic applications. - Aquino Ramos, José Agustín (2017)
The present project is on the synthesis of absorber material which belongs to IV- VI group viz Copper Antimony Sulfide thin films by spray pyrolysis technique. CuSbS2 has an ideal optical band gap of Eg=1.55 eV [1] that is suitable for photovoltaic applications. The spray pyrolysis technique is a chemical deposition that it does not need vacuum and also the process is carried at low temperatures near 500 C. We obtained good quality thin films of thickness under 1m using this low cost technique. In chapter one, Thin Film Solar Cells, it is mentioned how the first photovoltaic cell was born, and the theory of the Photovoltaic effect. It was shown the functionally of a typical pn junction solar cell, the PV structures and the configurations used in the photovoltaic industry. In chapter two, CuSbS2: a novel photovoltaic material, a summary on different types of deposition techniques for thin films is presented. Further, a detailed description on the spray pyrolysis method along with a complete theoretical views on the mechanism of the film growth process. Chapter three, Experimentation, begins with the problem approach, the justification of the present study, the objectives, and the proposed hypothesis. The chapter continues with the approach of experiments through a diagram of the prototype spray pyrolysis set up and the parameters that were considered for the synthesis process. Further, description of the characterization technique used for the present work are given. In chapter four, Characterization of CuSbS2 thin films, detailed analysis of the results is presented. In chapter five, Conclusions and recommendations, the important findings of the present research project are highlighted and also, further scope of the project.